$L^∞$ Convergence of Quasi-Conforming Finite Elements for the Biharmonic Equation (Journal of Computational Mathematics, 1995)
In this paper we consider the $L^∞$ convergence for quasi-conforming finite elements solving the boundary value problems of the biharmonic equation and give the nearly optimal order $L^∞$ estimates.